Analysis of Basalt Fiber Reinforced Polymer Concrete Cast Bed for Horizontal Machining Center - Zhang, Tao; Xu , Yun; Liao, Hailin; Zhang, Wenlu (International Journal of Mechanical and Electrical Engineering, 2025)
This study takes the bed of a vertical machining center as the research object, conducting static, dynamic, and comparative analyses between basalt fiber reinforced polymer concrete (BFPC) beds and cast-iron beds. Using SolidWorks software, 3D models were created according to the material characteristics of BFPC castings and cast iron. ANSYS software was then employed to perform static and dynamic analyses on both types of beds. Results demonstrate that under identical working conditions, the BFRPC bed exhibits lower deformation than the cast iron bed, effectively increases the natural frequency of the bed structure, and significantly reduces dynamic response when subjected to external excitation.